The Influence of Creativity on Incongruity-Resolution and Nonsense Humor Comprehension. Issue 1 (2nd January 2019) - Wu, Ching-Lin; Chen, Hsueh-Chih
Abstract : Both creativity and humor are high-level cognitive functions and complex concepts. Although creativity and humor are generally deemed positively correlated, it has been difficult to explicitly identify their relationship with each other. The cognitive process of creativity includes divergent thinking, insight, and remote association, whereas humor comprehension includes incongruity resolution and nonsense humor. The difference between the 2 types of humor is in whether individuals can understand the content of jokes through logical deduction. This study explored the relationship of the different dimensions of cognitive creativity and incongruity-resolution and nonsense humor comprehension. Furthermore, we examined the influence of divergent thinking, insight, and remote association on incongruity-resolution and nonsense humor comprehension. The scores from 103 participants on a divergent thinking questionnaire, an insight problem-solving task, and the Chinese compound remote associate problems test were used to analyze their comprehension of incongruity resolution and nonsense humor. The results showed a positive correlation between remote association and incongruity-resolution humor comprehension, as well as a positive correlation between insight and nonsense humor comprehension. These findings indicate that each dimension of cognitive creativity has a particular way of connecting to various types of humor comprehension.